2010
DOI: 10.1016/j.ijid.2010.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Clostridium tertium bacteremia: contamination or true pathogen? A report of two cases and a review of the literature

Abstract: We observed two cases of Clostridium tertium bacteremia three months apart in the sterile unit of our department of hematology and oncology. One patient was being treated for first-relapse acute myeloblastic leukemia, while the second was receiving high-dose chemotherapy with hematopoietic stem cell support for non-Hodgkin lymphoma. At the time that C. tertium was identified, the first patient was completely asymptomatic, while the second was highly febrile. Both responded biologically and/or clinically to ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
39
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(39 citation statements)
references
References 14 publications
0
39
0
Order By: Relevance
“…[4] Because of the fact that C. tertium is observed as both gram-positive and -negative bacilli, it can be misidentified as Corynebacterium or Bacillus species; thus, it usually takes considerable time to identify the species using classical bacteriological techniques. [2][3][4][5][6][7][8][9][10] Hence, in our case, we initially misidentified C. tertium as L. grayi.…”
Section: Discussionmentioning
confidence: 87%
See 4 more Smart Citations
“…[4] Because of the fact that C. tertium is observed as both gram-positive and -negative bacilli, it can be misidentified as Corynebacterium or Bacillus species; thus, it usually takes considerable time to identify the species using classical bacteriological techniques. [2][3][4][5][6][7][8][9][10] Hence, in our case, we initially misidentified C. tertium as L. grayi.…”
Section: Discussionmentioning
confidence: 87%
“…[6,10] However, fatal cases of C. tertium bacteremia have been reported [2,5,8] and we believe that treatment must be initiated upon the identification of the bacterium in blood cultures. To date, although most documented cases have involved neutropenic patients, [2,[5][6][7][9][10][11] cases involving non-neutropenic patients have also been described. [2,4,7,8] Salvador et al [11] reported that C. tertium could be rapidly identified using a novel mass spectrometry technology (matrix assisted laser desorption ionization timeof-flight).…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations